Implementation of the Principal's Policy Regarding Character Education at the As-Syafi'iyah Integrated Islamic Elementary School Pekanbaru - Desmasyari, Shelvi; AR, Hasnah Faizah; Gimin, Gimin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper examines the further implementation of the principal's policy regarding character education at the As-Syafi'iyah Integrated Islamic Elementary School Pekanbaru. The research uses a qualitative approach with descriptive methods. Data collection techniques use documentation, observation, and interviews. The research subjects involved school principals, foundations, committees, curriculum leaders, teachers, the community around the school, and students at SDIT As-Syafi'iyah Pekanbaru. The results show that 1) the principal's policy in implementing character education at SDIT As-Syafi'iyah Pekanbaru in terms of planning, organizing, implementing, and supervising has gone well. This is because the school principal has created a program to help the implementation of character values. In addition, 2) the description of the implementation of character education at SDIT As-Syafi'iyah Pekanbaru shows that both the principal and teachers at SDIT As-Syafi'iyah Pekanbaru pay attention to the character of students at school, even though there are still some students who are negligent sometimes. Furthermore, 3) supporting factors that can influence the formation of students' character are motivation, encouragement, and parental support. In the implementation of character education, there are still several inhibiting factors, including the fact that there are still some students who have less harmonious family backgrounds, the students' characters are different, and learning facilities are still lacking. In conclusion, 4) the solutions are being implemented in implementing character education values in SDIT As-Syafi'iyah Pekanbaru to overcome the problem of strengthening character education for students. The participation of students' parents at school are effort to ensure that the rules in the policy implementing character education are implemented well.